PREPARATION OF FINANCIAL STATEMENTS FOR FOUNDATIONS BASED ON ISAK 335: A CASE STUDY OF AL QAROMAH BERKAT ILAHI FOUNDATION - Helda Wati; Mahyuni Mahyuni (ADISAM Publisher, 2025)
This study aims to implement the financial statement preparation of a non-profit organization, Yayasan Al Qaromah Berkat Ilahi, in accordance with ISAK 335. The foundation previously only recorded cash inflows and outflows without compiling structured financial reports. Using a qualitative descriptive approach, data were collected through interviews, documentation, and observation. The results of this study indicate that the financial statements prepared based on ISAK 335 include a Statement of Financial Position, Statement of Activities, Statement of Cash Flows, Statement of Changes in Net Assets, and Notes to Financial Statements. The surplus in 2024 reached Rp204.359.950, indicating a strong financial performance and increased trust among stakeholders. This research encourages foundations to adopt ISAK 335 for transparency and accountability.